2009
DOI: 10.2174/092986709788186147
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells: A New Paradigm for Understanding Tumor Growth and Progression and Drug Resistance

Abstract: Normal somatic stem cells (SC) are naturally resistant to chemotherapeutic agents due to their expression of various membrane transporter molecules (such as MDR-1), detoxifying enzymes and DNA repair proteins. In addition, they also have a slow rate of cell turnover and therefore escape from chemotherapeutic agents that target rapidly replicating cells. Cancer stem cells (CSC), being the mutated counterparts of normal SC, also have similar properties, which allow them to survive therapy. These surviving CSC th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 0 publications
1
89
0
1
Order By: Relevance
“…7,8 The discovery of highly tumorigenic GSCs, which comprise a self-renewing subpopulation of GSCs, suggested that therapeutic approaches to effectively eradicate these cells may improve patient outcome. 9 Furthermore, present studies have demonstrated [10][11][12] that chemotherapy only destroys the most bulky cancer cells but cannot eradicate cancer stem cells (CSCs). The existence of CSCs leads to chemoresistance and tumor recurrence.…”
Section: Introductionmentioning
confidence: 98%
“…7,8 The discovery of highly tumorigenic GSCs, which comprise a self-renewing subpopulation of GSCs, suggested that therapeutic approaches to effectively eradicate these cells may improve patient outcome. 9 Furthermore, present studies have demonstrated [10][11][12] that chemotherapy only destroys the most bulky cancer cells but cannot eradicate cancer stem cells (CSCs). The existence of CSCs leads to chemoresistance and tumor recurrence.…”
Section: Introductionmentioning
confidence: 98%
“…The survival of cancer stem cells leads to chemoresistance and tumor recurrence. 23,24 Therefore, eradicating cancer stem cells may represent an effective chemotherapeutic strategy and thereby overcome tumor resistance.…”
Section: Introductionmentioning
confidence: 99%
“…В соответствии с этими представлениями опухоль организована иерархично, как нормальная ткань, с небольшой субпопуляцией недифференциро-ванных клеток, имеющих уникальные биологические свойства, необходимые для инициации, поддержания и распространения опухоли [14,15]. CSC расположены в нише с мезенхимальными клетками, которые обес-печивают выживание CSC, регулируют их пролифе-рацию посредством секреции растворимых факторов [16].…”
Section: пути канцерогенеза толстой кишкиunclassified